Ensino fundamental de nove anos: o impacto da política na escola - Tenreiro, Maria Odete Vieira (2011)
This work is dedicated to uncovering the impact of the educational policy of expansion of elementary schooling in the city of Ponta Grossa, Paraná, Brazil. The survey was conducted in 2009 in eight city schools. The chosen methodology was qualitative in approach and in terms of data organization we were inspired by the methodological procedure of Collective Subject Discourse (CSD), which made it possible to gather together individual thoughts of a similar nature into collective thought. In terms of data collection, semi-structured interviews were conducted in each of the selected schools with the school director, school manager and two classroom teachers who worked in the first year, totalling 30 individuals. The aims of this study are: to discuss the referrals that the Ponta Grossa Department of Education defined to organize the times and teaching spaces for the first year of elementary school (nine year-old students); and to understand the impact on elementary schooling of the policy of inclusion for six year-old children in public municipal schools. Chapter 1 outlines the existing work found on the subject that is recorded in the CAPES (Coordination of Improvement of Higher Education Personnel) database as well as pointing out the relevance of this research. Chapter 2 gives a brief history of the 1934 Constitution until the Constitutional Amendment 059/2009. Chapter 3 discusses the foundations of theoretical and methodological research, the paths followed in the search for empirical data, and the personal characteristics and professional training of those participating in the survey. Chapter 4 contains the core of the study and therefore includes the voices of the participants and an analysis of their discourses drawn from a reading of the didactic material. This provides not only the voices of the participants but also an interpretation of their discourses. Finally, the research shows that including children in school at the age of nine requires a political, administrative and pedagogical approach and the absence of these three factors makes it difficult to establish a policy. By ensuring that all children from the age of six have access to compulsory education is undoubtedly an opportunity to safeguard a right of citizenship. The survey also shows that the cut-off age for enrollment of children in the first year of elementary school inhibits the possibility of some children entering school. Among other results, we highlight: the need for a better physical structure to receive the children; pedagogical clarity regarding the work in year 1, the interplay between issues of early childhood education and elementary schooling; investment in training for teachers and all who work in schools, and fewer children in classrooms